Identification Of Skills Assessment Problems In Social Studies Subject - Waladul Mufid, M. Khoirul Annas; Purnomo, Agus; Adi, Khofifatu Rohmah (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Skills assessment is a teacher's obligation in learning based on the 2013 Curriculum (K13); its function is to measure the achievement of student learning outcomes. However, in reality, there are still many teachers who have not done it according to the guidelines. The focus of this research is to discuss the results of the initial identification of problems in the assessment of the realm of skills in K13. Data collection techniques with observation and interviews with social science subject teachers in Malang. Data from the interviews were analyzed using an interactive data analysis model consisting of four stages, namely (1) data collection, (2) presentation, (3) reduction, and (4) verification. The results show that the teacher still has difficulty in determining the appropriate assessment techniques. Besides, teachers also still do not know the reporting standards for the evaluation of skills; teachers also still do not know the standards for reporting the evaluation of skills. The follow-up implications for this research are in-depth interviews with more diverse informants relating to the problematic assessment of skills.